Pengaruh Pengungkapan Emisi Karbon Terhadap Harga Saham pada Rumah Sakit yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2019-2023 - Fauzi, Alamin; Nusa Bangsa, Ikrar; Ramadhan, Yanuar (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to determine the effect of carbon emissions disclosure on hospital share prices listed on the Indonesia Stock Exchange in 2019-2023. The method used in this research is quantitative descriptive. The sample used in the research was 6 hospitals with a research data period of 5 years, namely 2019-2023. The data analysis techniques used are descriptive analysis, simple linear regression analysis, and hypothesis testing. The research results show that carbon emission disclosure has a positive and insignificant effect on the share prices of hospitals listed on the Indonesia Stock Exchange for 2019-2023.